2020
DOI: 10.1177/1747954120966416
|View full text |Cite
|
Sign up to set email alerts
|

How playing area dimension and number of players constrain football performance during unbalanced ball possession games

Abstract: The aim of this investigation was to analyse the external workload, tactical individual actions of passing, and perceived internal load during unbalanced small-sided games. Ball possession formats (4v3, 4v4 and 4v5) were played in three different playing area dimensions (20 × 15m, 25 × 20m and 30 × 25m) by under-23 football players. Data were analysed under opposition-based perspective, by fixing one team (4vX), and by cooperation-based perspective according to teammates (4v2+X) for each playing area condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Other modifications (opponent ability level, game status, numerical team imbalance, periodization). Previous studies have shown that the tactical actions performed by players from different age groups are different, even when the task constraint is the same (Nunes et al, 2020;Travassos et al, 2018). For example, Figueira et al, (2018) assessed the impact of mixed aged players as a means of improving young players' tactical skills and physical fitness.…”
Section: Improving Tactical and Conditional Soccer Dimensionsmentioning
confidence: 99%
“…Other modifications (opponent ability level, game status, numerical team imbalance, periodization). Previous studies have shown that the tactical actions performed by players from different age groups are different, even when the task constraint is the same (Nunes et al, 2020;Travassos et al, 2018). For example, Figueira et al, (2018) assessed the impact of mixed aged players as a means of improving young players' tactical skills and physical fitness.…”
Section: Improving Tactical and Conditional Soccer Dimensionsmentioning
confidence: 99%
“…Previous research has revealed that the use of similar contexts of practice with players of different ages promoted variations on players' and teams' tactical actions. 6,7 For example, older players present higher values of area per team and stretching index 8 as well as higher distances between teams' centroids in SSGs 9 during SSGs in comparison with youngers.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that different players' roles require different perceptual and motor skills [18][19][20], it would be important to understand how the ball possession duration was affected according to these positions' specificities Accordingly, coaches have been using small-sided games (SSG), which consists of game-based situations performed in smaller spaces, with adapted rules and often with a fewer number of players. Considering that different rules emphasize different information [21,22], and consequently, different behaviours from the players, some research revealed that increasing the pitch area and playing in superiority stressed the passing actions [23], providing insightful information for coaches regarding on how to adjust the task constraints to emphasize ball possession. Despite the considerable amount of research exploring how different task constraints affects tactical behaviour of players and particularly ball possession, little is known how the manipulation of players capabilities and roles, constraints ball possession and the exploration of individual tactical actions.…”
Section: Introductionmentioning
confidence: 99%